(untitled) (Journal of Engineering, 2011)
Due to the popularity of radar, receivers often “hear” a great number of other transmitters in addition to their own return merely in noise. The dealing with the problem of identifying and/or separating a sum of tens of such pulse trains from a number of different sources are often received on the one communication channel. It is then of interest to identify which pulses are from which source, based on the assumption that the different sources have different characteristics. This search deals with a graphical user interface (GUI) to generate the radar pulse in order to use the required radar signal in any specified location.